2011
DOI: 10.3390/cancers3022597
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Photodynamyc Therapy Efficacy by Combination Therapy: Dated, Current and Oncoming Strategies

Abstract: Combination therapy is a common practice in many medical disciplines. It is defined as the use of more than one drug to treat the same disease. Sometimes this expression describes the simultaneous use of therapeutic approaches that target different cellular/molecular pathways, increasing the chances of killing the diseased cell. This short review is concerned with therapeutic combinations in which PDT (Photodynamyc Therapy) is the core therapeutic partner. Besides the description of the principal methods used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 144 publications
0
82
0
8
Order By: Relevance
“…The advantages of using combination therapy appear to lie in its combined targeting ability to different signal transduction pathways and enhanced approaches for combating drug resistance (Postiglione et al, 2011). Richard (Hara et al, 2005) reported that combination of low concentrations of TNF (1×10 2 IU/mL) and cisplatin has no obvious effects on caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using combination therapy appear to lie in its combined targeting ability to different signal transduction pathways and enhanced approaches for combating drug resistance (Postiglione et al, 2011). Richard (Hara et al, 2005) reported that combination of low concentrations of TNF (1×10 2 IU/mL) and cisplatin has no obvious effects on caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical use of PDT is still limited due to several issues. One approach which is being explored for the enhancement of the effectiveness of PDT involves the combination of a different therapeutic modality, such as surgery, chemotherapy and radiotherapy [25][26][27]. During the last twenty years of research, radiotherapy (based on the use of ionizing radiation) has been combined with PDT (based on the use of non-ionizing radiation), although conflicting results have been reported [28][29][30][31].…”
Section: New Approaches In Photodynamic Therapymentioning
confidence: 99%
“…Such mechanistically non-overlapping combinations of PDT with chemotherapy could overcome chemoresistance and potentially exert a synergistic effect in stubbornly refractive tumors. 156, 193, 212 Duska et al used the F(ab′) 2 fragment of OC-125 conjugated to a cationic poly-lysine polymer that was modified with multiple chlorin e6 (Ce6) PS molecules. 194, 208 This PIC was assessed in 5 human cancer cell lines as well as 19 primary cultures obtained from solid tumors and ascites samples derived from platinum-responsive and platinum-resistant OvCa patients.…”
Section: Photochemistry and Nanomedicine: Meeting Unmet Clinical Needsmentioning
confidence: 99%